NILAI-NILAI SPIRITUAL PENCAK SILAT KEBATINAN BERBASIS KEARIFAN LOKAL DALAM MERUBAH SIFAT PREMANISME - Widia Lestari; Annisa Fadillah; Rani Trianti; Dendi Septiawiguna; Asep Dahliyana (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
This research is to find out the spiritual values ​​ existing in Pencak Silat (Martial Arts) as an effort to develop one's character, one of which is able to change the nature of thuggery. This study uses a qualitative design with a case study method, in which researchers conduct observations and interviews, and collect documentation at Padepokan Sapu Jagat Sukabumi. The data analysis process was carried out through the stages of collecting scientific article data sources, listening and interpreting the results of interviews, and comparing the interpretation results with previous research. Pencak Silat itself is a cultural heritage of the Indonesian nation having spiritual values, an attitude of piety to God Almighty, and a good social character. The spiritual values existing in PadepokanSapu Jagat are, among others, teaching to always ask God’s forgiving (istigfar), to read syahadat (creed), salawat, talqin sentences, to say the names of Allah, and tawasul. In addition, PadepkanSapu Jagat also teaches its members how to control themselves. The results of observations and interviews conducted by researchers show that the spiritual value existing in Sapu Jagat Padepokan is, among others, the ability to change the attitude of former criminals in Sukabumi, in fact this Sapu Jagat Padepokan is committed to providing goodness to the community environment.